KESETARAAN GENDER DALAM PERSPEKTIF ISLAM: REINTERPRETASI FIQIH WANITA - Khariri Khariri (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Primary mission of Islam teaching are realizing prosperity to human being and liberating them fromall form of anarchy and injustice. Therefore, we need to reevaluate and questioning interpretation to Islamicteaching that inappropriate with justice and human rights values, example marginalizing women and genderinequality. Failure to interpreting al-Qur’an and Hadis will result discriminative woman fikih. It’s because patriarchyand misogynist understanding because authoritarianism phenomena, reader arbitrary reading to religious texts,mainly by puritans. There’s several thing to do to appropriating religious interpretation with humanity: first,interaction between writer, texts, and reader; second, consideration to normative and historic aspect, withhermeneutic nuance; third, contextual, comprehensive, and historic reading, also interpretation with holistic andinductive method